AKUNTABILITAS PELAYANAN PUBLIK (STUDI KASUS : PELAYANAN IZIN MENDIRIKAN BANGUNAN KOTA PEKANBARU) - Derry Surya Hamdani; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Accountability is a must for each public service department, Department of Spatial Planning and Building is a government agency that provide Building Permit License. People have to be satisfied of the service that given by this department. That is the reason why accountability is a must to accomplish this goal.This study aimed to describe Accountability Services Building Permit License (IMB) in Pekanbaru. The author uses indicators such as Reference Services, Solution Services and Priority Services to look at the accountability of public services. This study uses data collection techniques interview, observation and documentation.Results of this research is the accountability of service delivery Building Permit conducted by the Department of Spatial Planning and Building in Pekanbaru yet fully accountable, guides the work has not been completely oriented to service users, solution services provided to service users not provide facilities, and kepetingan service users yet fully prioritized.Keywords: Accountability, Building Permit